2013
DOI: 10.4236/epe.2013.54b071
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Wind Power Ramp Forecasting

Abstract: At home and broad, more wind power is being installed in electricity markets, the influence brought by wind power become more important on power system stability, especially the fluctuation, the uncertainty in wind power production and multi-time scale of the wind. In order to forecast ramp events before the power system encountering failure, so that the operator can adopt some limited controlling strategy. This paper introduces the present status of the wind power ramp prediction at home and abroad. And it gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 27 publications
2
31
0
1
Order By: Relevance
“…These results are also supported by other authors, who associate atmospheric phenomena (e.g., cold fronts and troughs) [4,8] as the critical weather situations for the TSO, namely to maintain the balance between production and consumption in order to ensure the stability of the power system, especially during the so-called "wind power ramp events" [9]. In fact, in [8] the authors suggest an automated cyclone detection algorithm for recognition of critical weather situations for wind power integration.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results are also supported by other authors, who associate atmospheric phenomena (e.g., cold fronts and troughs) [4,8] as the critical weather situations for the TSO, namely to maintain the balance between production and consumption in order to ensure the stability of the power system, especially during the so-called "wind power ramp events" [9]. In fact, in [8] the authors suggest an automated cyclone detection algorithm for recognition of critical weather situations for wind power integration.…”
Section: Introductionsupporting
confidence: 79%
“…According to [32], a wind power ramp occurs whenever there is a variation in energy production with considerable amplitude within a relatively short period of time. A power ramp can then be characterized by parameters [9] such as magnitude, lifetime, growth-rate, direction and occurrence time. In order to deploy a methodology capable of detecting wind power ramps, some definitions found in the literature were considered.…”
Section: Ramp Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al [16] derived the probabilistic distribution of ramps using stochastical scenarios of wind power generation, which were generated by an NN model trained using cumulative density function (CDF)-and auto-correlation function (ACF)-based objective functions. A thorough review of ramp forecasting can be found in [6,17].…”
Section: Related Workmentioning
confidence: 99%
“…Significant fluctuations are called ramps [158,159]. The ramps can be classified into up ramp where the power generated significantly increases in a short period and down ramp where the power generated significantly decreases in a short period [160].…”
Section: Chapter 7 Random Vector Functional Link Neural Network For Wmentioning
confidence: 99%